The pocket-creation method facilitates endoscopic submucosal dissection of gastric neoplasms involving the pyloric ring - Kitamura, Masafumi; Miura, Yoshimasa; Shinozaki, Satoshi; Sakamoto, Hirotsugu; Hayashi, Yoshikazu; Sakaguchi, Mio; Fukushima, Noriyoshi; Lefor, Alan Kawarai; Yamamoto, Hironori (Endoscopy International Open, 2021)
Background and study aims Endoscopic submucosal dissection (ESD) of superficial gastric lesions involving the pyloric ring is difficult. The pocket-creation method (PCM) with a small-caliber-tip transparent hood can overcome this difficulty by compressing the pyloric sphincter applying both traction and counter-traction. The aim of this study is to clarify the usefulness of the PCM for ESD of superficial gastric neoplasms involving the pyloric ring compared to the conventional method (CM).Patients and methods From October 2006 to August 2019, 66 gastric lesions requiring duodenal submucosal dissection beyond the pyloric ring in 66 patients were resected. The CM was mainly performed in the first period (CM group, n = 46) and the PCM in the second period (PCM group, n = 20). We retrospectively reviewed their medical records.Results Although no significant differences were observed in en bloc resection rates between the two groups, the PCM group had a significantly higher R0 resection rate than the CM group (P = 0.047). There were no holes in resected specimens in the PCM group while three specimens in the CM group had a hole. The dissection speed in the PCM group tended to be higher than in the CM group, although it did not reach statistical significance (P = 0.148). No significant differences were observed for the incidence of adverse events.Conclusions This is the first study reporting the advantages of the PCM over the CM for ESD of gastric lesions involving the pyloric ring. We believe that the PCM is an effective strategy to compress the pyloric sphincter and facilitates R0 resection.